(untitled) (Historia, 2021)
Power and resistance is an impressive book and one that makes a valuable contribution to South African historical In a historiography as poorly served by regional histories as ours, the publication of a compreheLsive, thoroughly researched and nuanced historical analysis of a particular region is a noteworthy occurrence. Switzer’s history of the Ciskei, is to my knowledge, the first regionally focused study to cover the entire span of South African history from pre-colonial times to the recent past. It also represents a rare attempt at synthesis within the revisionist tradition of South African historiography.